Praca fizyczna w życiu monastycznym: argumentacja św. Augustyna w De opere monachorum - Turek, Waldemar (Vox Patrum, 2018)
This article deals with manual labour in the life of monks as taught by St. Augustine in his treatise De opere monachorum. It describes the social context of the theme with particular reference to the situation in monastic communities of Carthage. Many monks in St. Augustine’s time were against manual labour. The article presents the structure of the Saint’s argumentation. St. Augustine clearly was in favour of the manual work of monks -and indirectly also of that of all Christians. The article analyses his exegesis of two Biblical texts (Mt 6:25-34 and 2Thess 3:10) that explain the need and beauty of work for daily spiritual growth. This is shown primarily on the basis of the teaching and example of the Apostle St. Paul, who was employed in various ways. Then the position of St. Augustine is discussed, according to whom the working monk gains the means of his support, cooperates with the Creator and continues His creative achievement. Work that allows the monk to attain some profit in temporal life and maintains the necessary equilibrium between the needs of the body and soul is shown above all to be a means for the attaining of the reward of eternal life. The monk, however, may be dispensed of manual labour, in part or even totally, in view of pastoral ministry, which plays a primary role in his vocation and mission.